Mapping and Functional Studies of Two Alloantibodies Developed in Patients with Type 3 von Willebrand Disease - Tout, Hélène; Obert, Bernadette; Houllier, Anne; Fressinaud, Edith; Rothschild, Chantal; Meyer, Dominique; Girma, Jean-Pierre (Thrombosis and Haemostasis, 2000)
Inhibitors against von Willebrand factor (vWF) developed in two unrelated multitransfused patients (patients 1 and 2) with severe (type 3) von Willebrand disease (vWD) were analyzed. Both inhibitors were identified as antibodies of the IgG class by ELISA using immobilized purified vWF and either serum or purified Ig from the patients. Typing, mapping and functional studies of both antibodies revealed significantly distinct properties. Patient 1 antibody contained all subclasses of IgG (1, 2, 3 and 4) whereas antibody from patient 2 was a mixture of only IgG1 and 4. By ELISA using a series of immobilized purified proteolytic fragments of vWF, patient 1 antibody mainly bound to fragment SpIII and, to a lower extent, to fragments SpII and SpI; it poorly bound to P34 and the 39/34 kDa fragment. In contrast, patient 2 antibody only bound to fragments corresponding to the N-terminal portion of vWF but failed to bind to SpII. Functional studies were performed by testing the capacity of each antibody to inhibit vWF binding to its various ligands. Both antibodies blocked vWF binding to Factor VIII (FVIII), fibrillar type III collagen, bitiscetin and the subsequent induced binding to GPIb. Patient 1 antibody also blocked vWF binding to platelet GPIb when induced by ristocetin. However it failed to block vWF binding to GPIb when induced by botrocetin as well as the binding of botrocetin itself to vWF. Our data thus suggest that this inhibitor does not recognize the GPIb-binding site on vWF but the sites of vWF involved in its interaction with ristocetin. In contrast, we observed that patient 2 antibody blocked vWF binding to platelet GPIb induced by either agonist as well as vWF binding to botrocetin. Finally, the effect of the antibodies was tested on vWF binding to GPIIb/IIIa. As expected from the mapping experiments, only IgG from patient 1 blocked the interaction while IgG from patient 2 had no effect. In conclusion, we have shown that two multitransfused patients with type 3 vWD have developed alloantibodies with similar properties to those of polyclonal antibodies but with distinct effects on the functions of vWF.
Keywords: Alloantibodies; vWF; binding; type 3 vWD